2010
DOI: 10.1254/jphs.10115fp
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potentials of an Artificial Oxygen-Carrier, Liposome-Encapsulated Hemoglobin, for Ischemia/Reperfusion-Induced Cerebral Dysfunction in Rats

Abstract: Abstract. We performed this study to elucidate whether a newly developed liposome-encapsulated hemoglobin, TRM-645 (TRM), can prevent cerebral dysfunction resulting from acute ischemic stroke when used as an oxygen carrier. Hippocampal long-term potentiation (LTP) in the perforant path-dentate gyrus synapses and anxiety-related behaviors in the elevated plus-maze test were evaluated as indices of cerebral functional outcomes in the rat with two-vessel occlusion (2VO), which was induced by 10-min clamping of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Several studies reported in the literature suggest the efficacy of Hb liposomes in the treatment of stroke by enhancing the biodistribution of Hb liposomes within the ischemic area in the brain. 144,145,147,[160][161][162][163][164]167,171,191,193,194 In the same way, liposomes for the delivery of angiogenic peptides 140 and VEGF 157 to promote angiogenesis in ischemic tissue were developed, and both formulations effectively promoted vascular regeneration. 140,157 Over the years, many liposomal formulations have been developed for the treatment of stroke.…”
Section: Stroke or Cerebral Ischemiamentioning
confidence: 99%
“…Several studies reported in the literature suggest the efficacy of Hb liposomes in the treatment of stroke by enhancing the biodistribution of Hb liposomes within the ischemic area in the brain. 144,145,147,[160][161][162][163][164]167,171,191,193,194 In the same way, liposomes for the delivery of angiogenic peptides 140 and VEGF 157 to promote angiogenesis in ischemic tissue were developed, and both formulations effectively promoted vascular regeneration. 140,157 Over the years, many liposomal formulations have been developed for the treatment of stroke.…”
Section: Stroke or Cerebral Ischemiamentioning
confidence: 99%
“…We recently reported that resuscitation with LEH was able to restore the brain metabolism in the rats with hemorrhagic shock (Rao et al, 2015). Others have also reported similar recovery of cerebral function by LEH infusion (Kakehata et al, 2010; Kaneda et al, 2014; Tiwari et al, 2010). However, the brain is protected, to a certain extent, against hypoxia and hypoperfusion by virtue of a physiologic diversion of blood flow from peripheral vascular network into the cerebral supply.…”
Section: Discussionmentioning
confidence: 56%
“…Given its physicochemical properties such as a small diameter and low viscosity, LEH has been studied not only as a blood substitute but also as a pharmacological agent for treating ischemic diseases. Several reports have demonstrated the efficacy of LEH in rat models of cerebral ischemia and in nonhuman primates . Furthermore, results of studies using imaging techniques in cerebral ischemia models indicated that LEH could distribute and deliver oxygen to ischemic tissues ; taken together, these results encourage the development of LEH for the treatment of ischemic stroke.…”
Section: Discussionmentioning
confidence: 88%